Optimization of Esterification and Transesterification Processes for Biodiesel Production from Used Cooking Oil - M. Hasan Abdullah; Wahyu Riyanto, Ong Andre; IBSW, Dyah Puspita (2477 - 6165, 2021)
Various treatments were carried out to produce biodiesel optimally. This research was conducted to process used cooking oil (UCO) into biodiesel. UCO with high FFA has saponification in the transesterification reaction. Transesterification experiment UCO with % FFA 4.261 and acid number 8.42 mg-KOH/g produced saponification. This experiment was carried out at different temperatures, speeds, and times. It is necessary to carry out initial esterification treatment. Simultaneously the biodiesel synthesis process is carried out by esterification and transesterification processes. The esterification process with 3%wt H2SO4 catalyst, 1:6 molar ratio of oil and alcohol with temperature treatment of 50 °C, speed of 300 rpm for 60 minutes can reduce % FFA in UCO to 2.115 and acid number 4.208 mg-KOH/g. The transesterification process using a NaOH catalyst of 0.5% wt, the molar ratio of oil and alcohol 1:6 with a temperature treatment of 60°C, a speed of 400 rpm for 60 minutes, can produce biodiesel with an acid number of 0.28 mg-KOH/g and 0.141 of % FFA according to SNI 7182-2015 standard. These results after purification on biodiesel.